2019
DOI: 10.1108/ijhcqa-05-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing organizational health literacy in a rural Missouri clinic: a qualitative case study

Abstract: Purpose The purpose of this paper is to evaluate a collaborative effort between a health care organization and academic institution to strengthen organizational health literacy. Design/methodology/approach The intervention took place at a rural, federally qualified health clinic in Missouri between May 2009 and April 2011. Qualitative interviews of key informants were conducted before (n=35) and after (n=23) the intervention to examine program implementation and success in effecting organizational change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…As part of the intervention, a library of plain language diabetes self-care materials for patients was created. Interviews conducted at the end of the intervention revealed that time was likely a barrier to creating additional health topic libraries and that providers often continued to select traditional materials (versus selecting from the library) for patients, although selecting materials with greater awareness of plain language [47]. If a database is created at the participating FQCHC, it will be important to convey the utility of the database to providers and also ensure that time is allotted to create and update the database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the intervention, a library of plain language diabetes self-care materials for patients was created. Interviews conducted at the end of the intervention revealed that time was likely a barrier to creating additional health topic libraries and that providers often continued to select traditional materials (versus selecting from the library) for patients, although selecting materials with greater awareness of plain language [47]. If a database is created at the participating FQCHC, it will be important to convey the utility of the database to providers and also ensure that time is allotted to create and update the database.…”
Section: Discussionmentioning
confidence: 99%
“…One of the organizational-level strategies discussed in the focus groups was the idea of having a centralized health information database, including websites, that could be used to provide patients with vetted materials in simple language. A qualitative study conducted in a federally qualified health clinic in Missouri revealed, as part of their needs assessment, that individuals who participated in the in-depth interviews (patients, non-clinical and clinical support staff, providers, administrators) thought that such a resource would be useful [ 47 ]. As part of the intervention, a library of plain language diabetes self-care materials for patients was created.…”
Section: Discussionmentioning
confidence: 99%
“…The 24 selected articles involved 17 original research projects (Table 1); several studies were part of larger research projects (these were: Grabeel [22], Grabeel [23], and Tester [24]; Beauchamp [25], Goeman [26], and Jessup [27]; Mabachi [28] and Brega [29]; Vellar [30] and Mastroianni; Weaver [31] and Wray [32]). We included some articles because, although they reported on a single domain, they were connected with other articles reporting different domains of the same study.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Together with the assessment, these studies also often evaluated the feasibility of the OHL-instrument. Eleven studies reported on both the assessment and on findings regarding the planning and delivery of interventions [22,[25][26][27][28][29][30][31][32][33][41][42][43]. Fourteen studies were conducted in the United States [22][23][24]28,29,[31][32][33][34]36,[38][39][40]43]; other studies were conducted in Australia [25][26][27]30,41], New Zealand & Canada [37], and several European countries including Austria [35], Italy [17], Ireland and the Netherlands [42], and Spain [3].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…We collected all data from 7 different countries, and 57% of studies were undertaken in the United States of America (USA) [ 34 , 35 , 36 , 37 ]. The first studies on OHL were conducted in 2006 [ 38 ] and others included articles that were published after 2012. We included 3 pilot studies [ 27 , 39 , 40 ], 3 cross-sectional studies [ 9 , 41 , 42 ], 2 case studies [ 34 , 37 ], 2 preliminaries [ 43 , 44 ], a comparative research piece [ 45 ], a workshop review [ 46 ], and a qualitative study [ 47 ].…”
Section: Resultsmentioning
confidence: 99%